24 season drums society management system - Sum, Yong Tat (2012)
24 Season Drums Society Management System is an online base management system to automate the managing process of society.The current system of the society is old traditional filing system to record the member profile, resources reservation,and attendance list and do not have a proper management system used and lack of proper platform for support and problem solving solution of member and open users.Therefore this system is develop for automate the managing process of society.There are three target users in this system,which are the administrator,society member and open users.This system has total of twenty main modules in this system, which is Manage donation,resource booking, resource availability,posting news and events, add comments to news & events, manual performance/show timetable,picture gallery, Search on photo, attendance management, management for society account,video gallery,search on video,manage members profile,request for show and performance, performance management, society complaint management,help and information,self timetable,resource/asset management and portal management.Adopting V-model in iterative and incremental development process is used to develop this project.There are separate to 2 phases which are verification phases and validation phases.In verification phases have requirement analysis,system design architecture design and coding.Validation phases have unit testing, integration testing,system testing and acceptance testing. The twenty modules will be divided to various independent parts by incremental development which is 6 divisions,the priority service of these incremental set also arranged in the order which the first set is the highest priority services.This system succeeds to achieve the objectives and solve the problems stated earlier.